Education and Textbooks (2016)
Education and textbooks have traditionally been standard objects of research in the history of science, technology, and medicine. However, they have often remained marginal in the formulation of large historiographical questions. In the last decades, the work of some historians of science has challenged this state of affairs. STEP has promoted a distinctive focus on education and textbooks, compared to other scholarship cultures such as the Anglo-American. This essay reviews its work in this field and stresses the potential of education and textbooks to produce interdisciplinary research in local, national, and international perspective.